Traditional cultural festivals and socio-economic boost: Evidence from the Ankos Masquerade Festival in Ghana - Fordjour, R.; Cruz, A. R. (African Journal of Hospitality, Tourism and Leisure, 2023)
Cultural events are largely associated with several socio-economic benefits for tourism destinations and host communities. This article explores the case of the Ankos Masquerade Festival (AMF), which takes place annually in Sekondi-Takoradi (Ghana). Although this area is known for its tourism potential, it still needs development to attract international tourism. The COVID-19 pandemic brought additional challenges as it stopped international travel and necessitated the cancellation of all types of events. In this context, the main objective of this article is to present a case study of the AMF to: (i) identify the profile of the foreign visitors/participants of the festival, their perceptions and their satisfaction level; (ii) understand the perceptions of stakeholders about the socio-economic potential of this event for the local community; and (iii) elaborate policy recommendations to inform and support the local authorities' decision-making. The AMF case study revealed new evidence about the relevance of this type of event for the development of cultural and creative tourism, for attracting international tourists, for improving the destination's image and for creating socio-economic benefits for local communities.